Remote ischemic preconditioning for reduction of ischemia-reperfusion injury after hepatectomy: a randomized sham-controlled trial - Hardt, Julia; Pohlmann, Paulina; Reißfelder, Christoph; Rahbari, Nuh Nabi (Surgery, 2024)
Background - Remote ischemic preconditioning reduces ischemia-reperfusion injury in patients undergoing hepatectomy. Moreover, there is evidence that the protective effects of remote ischemic preconditioning may be more pronounced in pre-damaged livers. The objective of this trial was to investigate the extent to which remote ischemic preconditioning can attenuate ischemia-reperfusion injury after hepatectomy and Pringle maneuver in patients with chronic liver disease. - Methods - In this randomized, controlled, triple-blind monocenter trial, a total of 102 patients with chronic liver disease and planned hepatectomy were enrolled between December 2019 and March 2022. Eligible patients were randomized to the remote ischemic preconditioning or sham arms. Remote ischemic preconditioning was induced through 3 10-minute cycles of alternating ischemia and reperfusion of the upper extremity. The study was prospectively registered in the German Clinical Trials Registry (DRKS00018931). - Results - A total of 102 patients were included in the study and were randomized (51 per arm). The median age was 69.5 years, approximately two-thirds of the patients were male (69/102, 67.7%), and the mean body mass index was 25.6 kg/m2. Most patients were classified as American Society of Anesthesiologists II (55/102, 53.9%) or III (45/102, 44.1%). The primary endpoint, the transaminases on the first postoperative day (alanine aminotransferase /aspartate aminotransferase: remote ischemic preconditioning arm: 250 (35-1721)/320 (42-1525) U/L versus sham control arm: 283 (32-792)/356 (20-1851) U/L, P = .820/0.639), clinical outcomes as well as remote ischemic preconditioning biomarker levels were comparable between both arms. - Conclusion - Remote ischemic preconditioning did not achieve a significant reduction in postoperative transaminase levels, nor did it affect clinical results and biomarkers.